REGISTER APPLICATION ON INSTAGRAM: BEAUTY PRODUCT - LEYLA CHRISTY SINAGA; IMMANUEL PRASETYA GINTINGS; JULI RACHMADANI HASIBUAN (LINGUISTICA, 2021)
In the era of globalization, seller-buyer transactions happened a lot on Instagram's social media platform. A register is a language variation that is usually used in the seller-buyer transaction. This study aimed to analyze the register in Instagram used in a beauty product by examining the linguistic form that is viewed from the register variable situation and understanding the meaning of register in a beauty product. This research uses qualitative research by collecting the data, analyzing the data, analyzing the context, and identifying the data. The object of this research is an Instagram account by guardian_id that was taken in February-March 2020. Based on the analysis, the researcher found 20 data with two types of linguistic form, the unstable situation of register that is field, tenor, mode, and two types of meaning in the register.